Orchid seed sensitivity to nitrate reflects habitat preferences and soil nitrate content. (9th October 2019) - Figura, T.; Weiser, M.; Ponert, J.
Abstract: Orchids are distributed around the world, however, the factors shaping their specific distribution and habitat preferences are largely unknown. Moreover, many orchids are at risk of becoming threatened as landscapes change, sometimes declining without apparent reason. One important factor affecting plant distribution is nutrient levels in the environment. Nitrates can inhibit not only orchid growth and persistence, but also seed germination. We used in vitro axenic cultures to exactly determine the germination sensitivity of seven orchid species to nitrates and correlated this with soil properties of the natural sites and with the species' habitat preferences. We found high variation in response to nitrate between species. Orchids from oligotrophic habitats were highly sensitive, while orchids from more eutrophic habitats were almost insensitive. Sensitivity to nitrate was also associated with soil parameters that indicated a higher nitrification rate. Our results indicate that nitrate can affect orchid distribution via direct inhibition of seed germination. Nitrate levels in soils are increasing rapidly due to intensification of agricultural processes and concurrent soil pollution, and we propose this increase could cause a decline in some orchid species. Abstract : The sensitivity of orchid seed germination to inhibition by nitrate reflects nitrate levels in natural habitats, indicating that nitrate could be one of the factors affecting orchid distribution.